Undercutting the future? European research spending in times of fiscal consolidation - Reinhilde Veugelers (Bruegel, 2014)
Innovation-lagging and fiscally weak countries in the European Union cut their public research and innovation (R&I) budgets during the crisis, while innovationleading and fiscally stronger countries forged ahead with public R&I spending. There is therefore an increasing research and innovation divide in Europe. The European Union, with its growing R&I resources managed by the European Commission can only partly redress this increasing divide. But the Commission has not used its powers to their full extent to allow member states in weak fiscal positions to maintain public R&I support. Furthermore, the application of fiscal rules has not taken R&I into consideration. Understanding the degree to which public R&I budgets in the EU have been used 'smartly' during the crisis and whether the European Commission has made 'smart' recommendations on public R&I as part of the European Semester, requires an assessment of the long-term impact on growth. Unfortunately, there have been few such assessment exercises. The European Commission should play a greater role in supporting member states in their consideration of public R&I for smart fiscal consolidation.
Keywords: 330